Heteroglossic ideologies in world Englishes: an examination of the Hong Kong context. (25th January 2016) - Jenks, Christopher J.; Lee, Jerry Won
Abstract : Much research in world Englishes centers on examining the linguistic features of a particular region. Such work can give the false impression of a collective homogeneous ideology of English within a geographic space. We refer to this limiting monolithic perspective of language ideology as 'the single linguistic narrative.' The present study builds on this body of work by investigating how often competing ideologies of English can circulate within a region. Focusing on the Hong Kong context, we adapt the concept of Bakhtinian heteroglossia to consider the simultaneous co‐presence of varying ideologies of English. Through an analysis of self‐narratives, we examine how Hong Kong university students construct expectations regarding how English should be used and what the colonial language means to their regional identity. Abstract :